A low frequency underwater sound propagation model - Stander, Marthinus Petrus (Department of Oceanography, 2016)
All wave-theoretic underwater sound propagation models attempt to derive the acoustic field originating from a sound source in a specific environment by either solving the wave equation directly or by solving an approximation there-of. This dissertation describes a normal mode direct solution with emphasis on the application as well as the theoretic analysis capability of the specific model, called NORMAN.